DISPUTE SETTLEMENT ON APARTMENT’S TRANSACTION - Fennieka Kristianto (Problematika Hukum, 2017)
The sale and purchase transactions of apartments in fact cause many problems between developers and consumers, so that the construction of apartments as the ultimate goal of providing housing is not achieved. This juridical normative research intends to examine a number of decisions regarding cases of disputes settlement over apartments’ unit transactions both through the court and outside the court. The main conclusion of this research is type of dispute over the apartments’ unit transactions (lawsuits qualification) determines the choice of dispute resolution and its consequences.